2015
DOI: 10.1007/s00402-015-2226-6
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between femoral tunnel location and graft bending angle in outside-in and transportal technique for ACL double bundle reconstruction in 3D-CT study

Abstract: Since the femoral tunnel exit in outside-in technique was located more anterior and proximal, femoral graft bending angle of AMB in outside-in technique was greater than that in transportal technique. Anterior position of the femoral tunnel exit in AMB increased femoral graft bending angle in outside-in and transportal techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 27 publications
2
33
0
Order By: Relevance
“…The significant correlation between anterior location of femoral exits and increased GBA support the conclusion that the more anterior exit points resulting from use of the flexible drill are the primary cause of the increased GBA. These results are consistent with a previous study that reported higher GBA and more anterior location of femoral exits with an outside-in drilling technique, compared to lower GBA with trans-portal drilling (which resulted in femoral exits at approximately the level of the lateral epicondyle) 40 . A study using computer simulation also concluded that more proximal location of femoral exits could reduce graft bending angles without changing the anatomic femoral and tibial aperture position 64 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The significant correlation between anterior location of femoral exits and increased GBA support the conclusion that the more anterior exit points resulting from use of the flexible drill are the primary cause of the increased GBA. These results are consistent with a previous study that reported higher GBA and more anterior location of femoral exits with an outside-in drilling technique, compared to lower GBA with trans-portal drilling (which resulted in femoral exits at approximately the level of the lateral epicondyle) 40 . A study using computer simulation also concluded that more proximal location of femoral exits could reduce graft bending angles without changing the anatomic femoral and tibial aperture position 64 .…”
Section: Discussionsupporting
confidence: 93%
“…A comparison study of trans-portal and trans-tibial ACL reconstruction reported that antero-medial and postero-lateral graft bending angles with trans-portal technique were significantly more acute (steep) than with single-bundle trans-tibial technique 33 . Recent studies comparing GBA between trans-portal and outside-in ACL reconstruction by postoperative CT have reported that outside-in technique resulted in even steeper graft bending than in trans-portal technique, with about 80° GBA 31,40,41 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26 Furthermore, Tomihara et al reported that the creation of a femoral aperture with a sharp edge due to a steep GBA of the PLB results in abrasive force and repetitive bending, which causes excessive mechanical stress on the bone-graft interface and may result in tunnel enlargement of the femoral PLB. 27 Shin et al reported that the tunnel length in patients with a mild GBA is increased compared with the tunnel length in those with a steep GBA. 28 The creation of a fixation point that is a long distance from the joint line leads to tunnel enlargement due to the "bungee cord effect."…”
Section: Discussionmentioning
confidence: 99%